2019
DOI: 10.1016/j.virol.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Porcine sapelovirus enters PK-15 cells via caveolae-dependent endocytosis and requires Rab7 and Rab11

Abstract: A B S T R A C TTo comprehensively understand the endocytosis of Sapelovirus A (PSV) entry into PK-15 cells, we studied PSV infection in the context of cell perturbations through drug inhibition, siRNA silencing and overexpression of dominant negative (DN) mutants. We showed here that PSV infection of PK-15 cells was unaffected by pretreated with chlorpromazine, EIPA, knockdown of the clathrin heavy chain or overexpression of Eps15 DN mutant. Conversely, PSV infection was sensitive to NH 4 Cl, chloroquine, dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Wortmannin is widely used in trafficking studies and has a different mechanism of blocking the endocytic pathway than amiloride, since it is a covalent inhibitor of phosphoinositide 3-kinases (PI3Ks), which are involved in multiple stages of macropinocytosis [ 90 , 91 ]. These results indicate that the internalization of the conjugate is independent of macropinocytosis but requires PI3Ks in a similar way to the process described by Zhao et al, 2019 [ 92 ].…”
Section: Resultssupporting
confidence: 84%
“…Wortmannin is widely used in trafficking studies and has a different mechanism of blocking the endocytic pathway than amiloride, since it is a covalent inhibitor of phosphoinositide 3-kinases (PI3Ks), which are involved in multiple stages of macropinocytosis [ 90 , 91 ]. These results indicate that the internalization of the conjugate is independent of macropinocytosis but requires PI3Ks in a similar way to the process described by Zhao et al, 2019 [ 92 ].…”
Section: Resultssupporting
confidence: 84%
“…In the past decades, it has been proved that many viruses can be internalized via clathrin‐ and caveolae‐mediated endocytosis by different methods. By using specific inhibitors, RNA interference, and dominant negative mutants, it has been indicated that hepatitis C virus, African swine fever virus, hepatitis E virus, and porcine hemagglutinating encephalomyelitis virus enter their host cells via clathrin‐mediated endocytosis, while grass carp reovirus and porcine sapelovirus enter their host cells via caveolae‐mediated endocytosis . In addition to these conventional methods, single‐virus tracking provides many new insights into the study of the virus endocytic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…PSV has been regarded as a causative agent of neurological, diarrheal, and fertility disorders in pig. Although the PSV receptor and entry pathway have been reported [5,18], the information of target proteins related to virus infection is largely unknown. Comparative proteomic analysis involving TMT has been widely used to explore host responses of various viral and fungal infections [9,19,20].…”
Section: Discussionmentioning
confidence: 99%